Continuous wall conditioning VHF discharge without magnetic field in a toroidal device - Lozin, A.V.; Moiseenko, M.M.; Kozulya, M.M.; Kramskoj, E.D.; Korovin, V.B.; Yevsyukov, A.V.; Grigor’eva, L.I.; Beletskii, A.A.; Shapoval, A.N.; Makhov, M.M.; Krasyuk, A.Yu.; Baron, D.I. (Вопросы атомной науки и техники, 2016)
Experiments were carried out at Uragan-2M torsaron for wall conditioning without magnetic field. Plasma discharge was created with the same antenna and VHF generator used for weak magnetic field (B0=100 G) wall conditioning. Experiment was carried out during whole wall conditioning period of Uragan-2M experimental campaign. The dynamics of wall conditioning was obtained alongside with standard plasma parameters measurements.